DIFFERENTIATED APPROACH TO THE SURGICAL EXTRACTION OF WISDOM TEETH - A.I. Pankevych; I.A. Kolisnyk; A.M. Hohol (Український стоматологічний альманах)
Impaction and malposition of wisdom teeth and associated inflammatory and tumor-like complications occur in 35-50% of the able-bodied population. The operation of surgical extraction of the third molar of the mandible is indicated for these patients and this operation is one of the most common in surgical dentistry today.Alsoasignificant indication for wisdom teeth removaliscrowding of teeth.